The association between screen time exposure and myopia in children and adolescents: a meta-analysis - Zhiqiang Zong; Yaxin Zhang; Jianchao Qiao; Yuan Tian; Shaojun Xu (BMC, 2024)
Abstract Objective This study aimed to systematically review epidemiological evidence on associations between screen time exposure and myopia in children and adolescents, and to quantitatively evaluate summary effect estimates from existing literature. Method There were three online databases including PubMed, Embase, and Web of Science, for epidemiological studies on screen time exposure and myopia published before June 1, 2023. The risk of bias was assessed by the Newcastle Ottawa Scale (NOS) checklist. Summary odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate the correlation between screen time exposure and myopia using random or fixed-effect models by exposure type (categorical/continuous). We also performed subgroup analysis by screen device type, study quality, geographic region, and research period. Results We searched 7,571 records from three databases and identified 19 eligible studies, including 14 high-quality studies and 5 moderate-quality studies. Meta-analyses suggested that there was a statistically significant correlation between screen time (high vs. low) and myopia. The pooled ORs with 95%CIs were respectively 2.24 (1.47-3.42) for cross-sectional studies, and 2.39 (2.07-2.76) for cohort studies. We also found a significant association between continuous exposure to screen time (per 1 h/d increase) and myopia in cohort studies. The pooled ORs with 95%CIs were 1.07 (1.01-1.13). In subgroup analysis stratified by screen device type in cross-sectional studies, screen time exposures from computers (categorical: OR = 8.19, 95%CI: 4.78-14.04; continuous: OR = 1.22, 95%CI: 1.10-1.35) and televisions (categorical: OR = 1.46, 95%CI: 1.02-2.10) were associated with myopia, while smartphones were not. Although publication bias was detected, the pooled results did not show significant changes after adjustment using the trim and fill method. Conclusion Our findings support that screen time exposure was significantly associated with myopia in children and adolescents. Notably, screen time exposure from computers may have the most significant impact on myopia.